PTU-056 Generalist vs specialist: does dedicated endoscopy in barrett's oesophagus yield improved adherence to BSG guidance?. (June 2019) - Stroud, Samuel; Basu, Kumar
Abstract : Introduction: Barrett's oesophagus (BO) is a premalignant precursor of oesophageal adenocarcinoma (OAC). 1 With yearly progression seen in 0.3-0.6/100 patients, a robust surveillance strategy is crucial. 1 The British Society of Gastroenterology (BSG ) 2013 guidance recommends the use of two techniques for reviewing non-dysplastic BO: (1) Prague Classification and (2) Seattle Biopsy Protocol. 2 A retrospective analysis (2014–2015) at a large teaching hospital showed correct use of 'Prague Classification' and 'Seattle Biopsy Protocol' to be 32% and 42%, respectively. Subsequently, recommendations to introduce specialist (operators with BO interest who are highly familiar with BSG guidance) endoscopy as well as improving the general familiarity with the BSG guidance were proposed. This study aimed to evaluate (1) overall compliance to guidance for both techniques, (2) differences between specialist and generalist operators, and (3) availability of specialist endoscopy. Methods: Data collection spanned 16 months (1/1/2016-30/4/2017) with 442 patients being identified from the Infoflex endoscopy database. Patients were enrolled if the main indication for upper gastrointestinal endoscopy was coded as 'Barrett's surveillance'. Review of histology reports, Infoflex accounts and clinical notes allowed acquisition of both 'Prague Classification' and 'Seattle Biopsy Protocol' data, alongside operator status (generalist or specialist). The relationship between type of endoscopy and compliance to techniques were assessed statistically through chi-squared independence testing. Results: From 442 cases (Mean 66.2 years (Range 24–88)), compliance to both 'Prague Classification' and 'Seattle Biopsy Protocol' were 73% (322/442) and 70% (309/442), respectively. Access to specialist endoscopy was improved at 41% compared to 26% (2014-2015). Furthermore, specialist endoscopy yielded superior adherence to both, 'Prague Classification' (87%, (157/181) v 63%, (165/261); X 2 =31.04, p<0.0001)) and 'Seattle Biopsy Protocol' (75%, (136/181) v 66%, (173/261); X 2 =4.09, p=0.0432)), compared with generalist counterparts. Conclusions: Specialist endoscopy improves adherence to BSG recommendations. The introduction of dedicated specialist lists at this large teaching hospital will help to optimise surveillance further. Ultimately, future work is necessary to help identify whether this specialist service carries value for both, BO screening and outcomes related to oesophageal dysplasia and OAC. References: De Jonge PJF, et al. Barrett's oesophagus: epidemiology, cancer risk and implications for management. GUT, BMJ . 2014;63:191–202. Fitzgerald RC et al . British society of gastroenterology guidelines on the diagnosis and management of Barrett's oesophagus. Gut, BMJ. 2013;0:1–36.